EVALUATION OF THE STATUS OF SALIVARY NITRIC OXIDE IN PATIENTS WITH DENTAL CARIES - Hegde, Mithra N.; Kumari, Suchetha; Hegde, Nidarsh; Shetty, Shilpa; Nireeksha (Journal of Health and Allied Sciences NU, 2012)
The aim of the present study is to evaluate the status of salivary nitric oxide in patients with dental caries. The study consisted of 80 individuals. According to DFMT index, the subjects were divided into control group (DMFT=0) and study group (DMFT>5). Saliva sample was collected from each subject. Nitric oxide concentration was measured as total nitrates and nitrites by the Griess reaction method. The results of this study show that the presence of NO and its metabolites in saliva of adults with natural healthy teeth is significantly higher compared to high risk group, suggesting the protective role of NO in relation to caries. From the study it can be concluded that highly significant increase of nitrates and nitrites in stimulated saliva of high caries risk group could be the host defense response opposing bacterial growth. The obtained results support the role of NO as modulator of bacterial proliferation and suggest that increased NO production might contribute to lower caries incidence in adults.
Keywords: Nitric Oxide; Dental Caries; Saliva; DMFT